2022
DOI: 10.17159/2413-3108/2022/vn71a9539
|View full text |Cite
|
Sign up to set email alerts
|

Understanding crime using GIS and the context of COVID-19: the case of Saldanha Bay Municipality

Abstract: South Africa faces high levels of crime. The Saldanha Bay Municipality, the setting of this study, is laden with poverty, unemployment and gangsterism that deprive quality of life and contribute to social ills. While crime management and prevention strategies require information regarding crime trends, this information for the Saldanha Bay Municipality area is limited. Hence, the study aimed to illustrate the spatial distribution and trends of crime in the Saldanha Bay Municipality, focusing on the period Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are various reasons why crime especially violent crime is prevalent, among others, the common causes are: poverty, unemployment, economic inequalities between the rich and poor, lack of education, population density (Henrico et al, 2022;Mathuthu, 2019;Bower Du Toit, 2014;Hull, 2000). Unemployment in (SA 32,7%) has been confirmed through empirical research, by Tshabalala, where the findings revealed that most of the people who commit crime are not only unemployed but are married, which indicates that their crimes are motivated by a pressure to provide for their families (Tshabalala, 2014).…”
Section: Causes Of Crimementioning
confidence: 99%
“…There are various reasons why crime especially violent crime is prevalent, among others, the common causes are: poverty, unemployment, economic inequalities between the rich and poor, lack of education, population density (Henrico et al, 2022;Mathuthu, 2019;Bower Du Toit, 2014;Hull, 2000). Unemployment in (SA 32,7%) has been confirmed through empirical research, by Tshabalala, where the findings revealed that most of the people who commit crime are not only unemployed but are married, which indicates that their crimes are motivated by a pressure to provide for their families (Tshabalala, 2014).…”
Section: Causes Of Crimementioning
confidence: 99%
“…The Getis-Ord Gi* statistical model was applied to calculate Z-scores and p values for each point location to represent the COVID-19 incidence intensity. The ArcGIS Getis-Ord Gi* statistics tool was used to show the hotspot mapping and illustrate the spatial distribution and trends of crime in the Saldanha Bay Municipality [33]. These studies indicate the aggregation and stability of crime hot spots.…”
Section: Introductionmentioning
confidence: 99%